K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 11 2024

Ta có: \(25-\left(x+3\right)^2=9\)

=>\(\left(x+3\right)^2=25-9=16\)

=>\(\left[{}\begin{matrix}x+3=4\\x+3=-4\end{matrix}\right.\)

=>\(\left[{}\begin{matrix}x=4-3=1\\x=-4-3=-7\end{matrix}\right.\)

26 tháng 11 2024

  25 - (x + 3)2 = 9

         (x + 3)= 25 - 9

         (x + 3)2 = 16

   Hay (x + 3)2 = 42

⇒x + 3 = 4

⇒x = 1 ϵ Z

    Vậy x = 1

21 tháng 3 2020

a,11-(15+21)=x-(25-9)

      11-15-21=x-25+9

               -x=-25+9-11+15+21

               -x=9

                x=-9

b,9-25=(7-x)-(25+7)

    -16=7-x-32

      x=7-32+16

     x=-9

28 tháng 12 2015

(7-x)-32=-16

7-x=-16+32

7-x=16

x=7-16

x=-9

28 tháng 12 2015

 9 -25 = (7-x) - ( 25 +7)

 - 16 = 7 -x - 32

x = 7 -32 +16 

x =7 -16

x = - 9

11 tháng 8 2016

9-25            =(7-x)-(25+7)

(7-x)-(25+7)=9-25

x               =7-9-25-7+25

x               =-9

11 tháng 8 2016

9 - 25 = (7 - x) - ( 25 + 7)

-16 = 7 - x - 32

-16 = -25 - x 

x = -25 - (-16)

x = -25 + 16

x = -9

21 tháng 1 2018

Giải

                          9 – 25 = ( 7 – x ) – ( 25+7)

                      9 +( -25) = 7 – x – 25 – 7

                               -16 = 7 – x – 25 – 7

                                  x = 7 – 7 – 25 +16

                                  x = - 25 + 16

                                  x = -9 


 

21 tháng 2 2021

a, 11 - ( 15 + 11 ) = x - ( 25 - 9 )

11-15-11=x-25+9

-15=x-16

x=1

b, 2 - x = 17 - ( - 5 )

2-x=22

x=-20

c, x - 12 = ( - 9 ) - 15

x-12=-24

x=-12

d, 9 - 25 = ( 7 - x ) - ( 25 + 7 )

(7-x)-32=-16

7-x=16

x=-9

#H

11 tháng 6 2019

Đáp án là D

34 - (25 + 34) = x - (25 - 9)

34 - 25 - 34 = x - 16

34 - 34 - 25 = x - 16

-25 = x - 16

-25 + 16 = x

-(25 - 16) = x

-9 = x

1 tháng 2 2018

9 – 25 = (7-x) – (25 + 7)

9 + (-25) = 7 – x – 25 – 7

-16 = 7 – x – 25 – 7

X = 7 – 7 – 25 + 16

x = -25 + 16

x = -9

17 tháng 12 2015

11 - 15 - 11 = x - 25 + 9

-15 = x - 16

-15 + 16 = x

=> x = 1

17 tháng 12 2015

11-(15+11)=x-(25-9)

x-16=11-26

x-16=-15

x=-15+16

x=1

28 tháng 11 2015

11-(15+11)=x-(25-9)

11-26=x-16

-15=x-16

x= -15+16

x=1

vậy x=1

tick nha !!!!!!!

28 tháng 11 2015

Ta co : 

11-(15+11)=x-(25-9)

-15=x-(25-9)

-15=x-16

x=-15+16

x=1

lik e nhe